Correlation of self-efficacy, social support, and learning interest with students' metacognitive skills in biology learning - Dinar, Sri Putri; Bahri, Arsad; Ismail, Ismail (JPBIO (Jurnal Pendidikan Biologi), 2025)
Metacognitive skills are a person's ability to manage cognition and make decisions to solve problems. Therefore, this study aims to determine the relationship between self-efficacy, social support, and interest in learning biology with students' metacognitive skills. This type of research uses the ex-post facto method with a quantitative approach. The research sample consisted of 271 students of class XI of a public high school in Tamalate District, Makassar City. The research instruments were questionnaires and essay questions. Data were analysed by path analysis using IBM SPSS Statistics 29.0 for Windows. The results of study indicate that self-efficacy has a relationship with interest in learning biology, social support has a relationship with interest in learning biology, self-efficacy has a relationship with metacognitive skills, social support has a relationship with metacognitive skills, interest in learning biology has a relationship with metacognitive skills, self- efficacy has an indirect relationship (through interest in learning biology) to metacognitive skills, social support has an indirect relationship (through interest in learning Biology) to students' metacogitive skills. Based on the research findings, it is known that many aspects can affect metacognitive skills, so it is necessary to consider the empowerment of metacognitive skills seriously.